2017
DOI: 10.1002/ece3.3277
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of photosynthesis‐related traits of 27 abundant or subordinate bryophyte species in a subalpine old‐growth fir forest

Abstract: Bryophyte communities can exhibit similar structural and taxonomic diversity as vascular plant communities, just at a smaller scale. Whether the physiological diversity can be similarly diverse, and whether it can explain local abundance patterns is unknown, due to a lack of community‐wide studies of physiological traits. This study re‐analyzed data on photosynthesis‐related traits (including the nitrogen, phosphorus and chlorophyll concentrations, photosynthetic capacities, and photosynthetic nutrient use eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Photosynthetic capacity and light adaptability were greater in P. inflexum , indicating its high irradiance tolerance due to its dense turf life‐form, thicker cell wall, and surface‐wax layers that reduce water loss (Proctor, ). These features are reflected in the wide ecological and geographical distribution of Polytrichaceae mosses (Corradini and Clément, ) and their role as pioneer species in managed open habitats (Bao, ; Wang et al., 2017a). In contrast, the cushion life‐form species, L. juniperoideum , which is known to be well adapted to low‐light environments (Wang et al., ), had higher photosynthetic capacity and larger leaves and cells, indicating greater adaptability to shade conditions, but lower adaptability to intense irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthetic capacity and light adaptability were greater in P. inflexum , indicating its high irradiance tolerance due to its dense turf life‐form, thicker cell wall, and surface‐wax layers that reduce water loss (Proctor, ). These features are reflected in the wide ecological and geographical distribution of Polytrichaceae mosses (Corradini and Clément, ) and their role as pioneer species in managed open habitats (Bao, ; Wang et al., 2017a). In contrast, the cushion life‐form species, L. juniperoideum , which is known to be well adapted to low‐light environments (Wang et al., ), had higher photosynthetic capacity and larger leaves and cells, indicating greater adaptability to shade conditions, but lower adaptability to intense irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the role of functional traits in bryophytes have focused on terricolous species (Wang et al., , Wang et al., , b; Coe et al., ) or bole epiphytic species in the understory (Song et al., ; Chen et al., ). To date, only one study has focused on functional traits of bryophytes along vertical gradients in a lowland wet forest and demonstrated correlations between photosynthetic traits and morphological traits (Waite and Sack, ).…”
mentioning
confidence: 99%
“…This is in accordance with the plant strategy theory which explicitly describes transitions between the different life strategies (During, ; Grime, ). According to results of Wang, Bader, Liu, Zhu, and Bao (), the intermediary life strategies of Polytrichum and Plagiomnium may be explained by specialized traits related to photosynthesis and growth forms.…”
Section: Discussionmentioning
confidence: 99%
“…Trait‐based studies on bryophytes have illustrated the diversity of morphological and physiological traits across species, clades (Kraichak, ; Waite & Sack, ; Wang, Bader, Liu, Zhu, & Bao, ; Wang, Bao, Feng, & Lin, ), sexes (Shaw & Gaughan, ; Slate, Rosenstiel, & Eppley, ), and within the diverse genus Sphagnum (Rice, Aclander, & Hanson, ). These studies have demonstrated how suites of physiological, morphological, and structural traits in bryophytes can be intercorrelated and also illustrate how variable some traits can be within and among species.…”
Section: Introductionmentioning
confidence: 99%
“…Also, certain physiological traits (i.e., light‐saturated photosynthetic rate and chlorophyll content) are often correlated with light environment (Marschall & Proctor, ; Waite & Sack, ), but, unlike vascular plants, these physiological traits are not consistently correlated with N content (Rice et al, ; Wang et al, ). To date, no trait‐based analyses have fully explored photosynthetic traits in bryophytes beyond basic light response and C assimilation (e.g., Rice et al, ; Wang et al, ). Examining characteristics of photosynthetic efficiency (e.g., using the chlorophyll fluorescence parameter F v / F m , the maximum quantum yield of photosystem II) and ecologically relevant C fixation traits (e.g., C‐balance) may uncover examples of novel physiological traits.…”
Section: Introductionmentioning
confidence: 99%